THE PARTICIPATION OF THE COMMUNITY IN FULFILLING THE NEED OF DOMESTIC PLAIN WATER IN GUNUNGKIDUL REGENCY - HILDERCARD SRI WAHYUNI (NIM 25407080), VINCENSIA
The available water, which is reachable and continual, becomes the most important part of life for anyone who lives in the city or village. The population that is continually growing up, from time to time needs a serious effort to make them aware to be sure that the source of water will always be available and continual. The development of domestic plain water infrastructure using communal system and people participation approach constitutes the alternative strategy in developing the area. This study researches the characteristics of the participation in case of types, forms and levels of participation in every session of the activities, and factors that form them. The study also investigates the occurrence of the relationship between participation characters and the successful of providing plain water infrastructure. The aim of the research is to understand the participation of the community that supports the providing of plain water. The result of the study is expected to describe the implementation of the activity of providing plain water infrastructure mentioned previously. It is also as an alternative to provide plain water infrastructure by the community that may suggest people with the participation theory and give information to other society who carry out the same activity in other places. In order to understand the characteristics of public participation in the activity, a descriptive analysis has carried out in case of quality and quantity in several sessions. The first session is to describe the occurrence of the participation and the level of success to provide plain water infrastructure. The second session is to compare the characteristics of participation occurred with the level of success to provide plain water infrastructure. The third session is to find the factors that form the characteristic of participation, either from individual character or groups characters factors. Finding the individual character factors is done by using chi square statistic analysis, within which using the cross-tab method to see the contingency coefficient and the significant level. Group character factors are reached by comparing the participation character that occurred with the each characteristics of the group being studied. The result of the study shows that the participation character is able to support the success of plain water infrastructure, in overall participation of the community. They actively and spontaneously donate anything in every stage of making decision. This participation happens when people in the society have close relationship and know one another. Organization that involves the community becomes an activator, there is a cost sharing between the society and the institution donators. And the people must become the first factor in making decision through every aspect like community, organization staff, and village leader, independent institution in which the members are its community. As a suggestion to the owner of the activities above with communal system is to mobilize the people intensively in every community activity and also to create public activity in order to increase the interaction among the society. Whereas, to create group characteristic that is able to grow up people participation, is suggested to give task to the organization of the society to distribute all the donations. So the society will have self-belonging to any activities in their community. Apart from this, all the funds should not be from outsiders donation, but there should be a cost sharing so it grows a self-belonging of the society to the activities and the responsibility to keep and maintain the infrastructure together. The group also needs to involve the society in every formal discussion and they have the right to make decision so they feel having responsibility on the decision they made. The infrastructure would be better managed by independent institution that also involves leaders of society and village leader. The approach of people participation in development activities is as a bottom up planning that can form a strategy in developing an area. The short aim of this approach is implement any single activity in the society together in order to fulfill the practical needs and to develop the prosperous of the society. Whereas the long term aim of the approach is to reach the efficiency of the society and increase the social life so the people can find their own potency and are courageous to act in order to make up the quality of their lives through learning continuously.